2014
DOI: 10.1179/0075891414z.00000000040
|View full text |Cite
|
Sign up to set email alerts
|

Variability within consistency: cairns and funerary practices of the Late Neolithic/Early Chalcolithic in the Al-Thulaythuwat area, southern Jordan

Abstract: Exploration undertaken in Al-Thulaythuwat/Jabal Kabd area, in the framework of the south-eastern Badia Archaeological Project, identified an extensive funerary phenomenon dating back to either, the Late Neolithic, or a transitional Late Neolithic/Early Chalcolithic phase. Excavation of a small but representative sample of burial structures, along with an analysis of the cairns and associated structures, highlighted different levels of variability. However, when viewed as a whole, this necropolis on the south-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…While no exact equivalent exists and the unique character of mustatils must be emphasised, there may be some form of relationship between mustatils and two forms of structure in the southern Levant. Firstly, there are the rectangular platforms associated with late Neolithic cairns, as previously mentioned at the start of this paper ( Abu-Azizeh et al, 2014 ). Secondly, ‘cultic’ sites, often described as shrines and sanctuaries, have been recorded across the arid southern Levant (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While no exact equivalent exists and the unique character of mustatils must be emphasised, there may be some form of relationship between mustatils and two forms of structure in the southern Levant. Firstly, there are the rectangular platforms associated with late Neolithic cairns, as previously mentioned at the start of this paper ( Abu-Azizeh et al, 2014 ). Secondly, ‘cultic’ sites, often described as shrines and sanctuaries, have been recorded across the arid southern Levant (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cairns – typically relatively small structures with a funerary function (e.g. Abu-Azizeh et al, 2014 ; Alsharekh, 2006 ; Guagnin et al, 2020 ; Harrower et al, 2013 ) – are found across the region and occurred from the Neolithic to at least ca. 600 AD ( Alsharekh, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations